STUDI PENERAPAN CRITICAL PATH METODE (CPM) PADA PROYEK PEMBANGUNAN PABRIK SEMEN REMBANG PT SEMEN GRESIK - Wasito Wasito; Ahmad Yani Syaikhudin (J-MACC, 2020)
The process of planning and project control during the execution of the construction project work is an important part of the project. Because time is limited by the project management work schedules are determined so that the leaders involved in the project should be able to anticipate changes in conditions. The failure of a project can be caused by poor planning and control are less effective, so that the project activity is not efficient. Doing so may result in delay time, declining quality, and the rising cost of implementation. Conversely, careful planning and effective control will bring the project to success.Critical path method (CPM) is one option that is right for project management to control the project completion time effective and efficient. In order to reduce the impact of delays and cost overruns of the project budget can be done with three alternative acceleration process control; (I) Addition of labor, (ii) Overtime, (iii) Subcontract. Acceleration duration is done on the works is in the critical path.